2021
DOI: 10.1038/s41598-021-95239-5
|View full text |Cite
|
Sign up to set email alerts
|

Telomere associated gene expression as well as TERT protein level and telomerase activity are altered in the ovarian follicles of aged mice

Abstract: Telomeres cap the ends of eukaryotic chromosomes to maintain genomic stability and integrity during an organism’s lifespan. The length of telomeres inevitably shortens due to DNA replication, genotoxic agents, and biological aging. A limited number of cell types, e.g., stem cells, germline cells, and early embryos can elongate shortened telomeres via the enzymatic action of telomerase, which is composed of telomerase reverse transcriptase (TERT) and telomerase RNA component (Terc). Additionally, telomere-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Clinical studies have also found that the length of telomeres in the granulosa cells of POI patients is significantly shorter, and that telomerase activity is significantly reduced [ 64 ]. Telomere damage was also observed in naturally aged ovarian cells, along with reduced expression levels of telomerase (TERC), telomeric reverse transcriptase (TERT) and telomere-related proteins (TRF1, TRF2, POT1) [ 65 , 66 ]. The relative length of telomeres in cumulus cells is closely related to oocyte and embryo quality and can be used as a potential marker for screening high-quality oocytes in the field of assisted reproductive technology (ART) [ 67 ].…”
Section: Pathological Mechanisms Related With Os In Ovarian Agingmentioning
confidence: 99%
“…Clinical studies have also found that the length of telomeres in the granulosa cells of POI patients is significantly shorter, and that telomerase activity is significantly reduced [ 64 ]. Telomere damage was also observed in naturally aged ovarian cells, along with reduced expression levels of telomerase (TERC), telomeric reverse transcriptase (TERT) and telomere-related proteins (TRF1, TRF2, POT1) [ 65 , 66 ]. The relative length of telomeres in cumulus cells is closely related to oocyte and embryo quality and can be used as a potential marker for screening high-quality oocytes in the field of assisted reproductive technology (ART) [ 67 ].…”
Section: Pathological Mechanisms Related With Os In Ovarian Agingmentioning
confidence: 99%
“…The data in the present study also indicate that TERT expression alters in GCs with aging, but RNA-sequencing data (data not shown) did not detect any significant changes in TERT expression between old and young human oocytes. Kosebent and Ozturk ( 38 ) suggested that TERT expression was differentially expressed at different developmental follicular stages in both young and old mice. These seemingly discordant results indicate that the regulation of TERT expression is tissue- and stage-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, telomerase activity in GCs is controlled by growth factors and female steroid hormones ( 29 ). The TERT gene promoter contains an estrogen response element ( 38 ). The microenvironment of GCs contains estrogens that are reported to influence telomerase activity and length ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a lack of TA and shorter telomeres have been found in granulosa cells of women with occult ovarian insufficiency [27] and in women with primary ovarian insufficiency [28]. Recent evidence shows a decrease in telomere length, shelterin genes and TERT expression, from fetal to postmenopausal life in ovaries and follicles of both murine models [29 ▪ ,30] and humans [31]. In contrast, higher TA has been found in cumulus cells of women with polycystic ovary syndrome as they have a high number of small antral follicles [32].…”
Section: Ovarian Agingmentioning
confidence: 99%